176 Source of social support and post-injury depression and anxiety among college student-athletes. (5th May 2020) - Sullivan, Lindsay; Ding, Kele; Tattersall, Heather; Yang, Jingzhen
Abstract : Purpose: To examine the effects of different sources of social support (team vs. family/friends) during recovery from injury on post-injury depression and anxiety symptoms among college student-athletes. Methods: College student-athletes from two Big 10 universities were prospectively enrolled at the beginning of the 2007–2008 through 2011–2012 sport seasons and followed for injury. Depression and anxiety scores were assessed at baseline and at multiple time points post-injury until return-to-play. Linear mixed models were used to examine the effects of social support from family/friends or from the team (coaches, athletic trainers, and teammates) during recovery, along with satisfaction with the support received, on changes in post-injury depression and anxiety scores. Results: A total of 597 injuries (sustained by 397 athletes) were included in the analysis. Of these injuries, 67% occurred in males, 39.9% occurred during football, and 11.9% were concussions. Average depression and anxiety scores at baseline were 10.7 and 41.3, respectively. Results showed that the quantity of social support received from family/friends during recovery significantly influenced post-injury depression scores (β=0.60, p=0.028). No such relationship was found between social support received from the team and depression scores. Furthermore, overall satisfaction with social support received during recovery, regardless of the source of social support, was negatively associated with post-injury scores in depression (p<0.01) and anxiety (p<0.01). Conclusion: College student-athletes' satisfaction with the social support received from both family/friends and one's team post-injury was negatively associated with post-injury depression and anxiety scores. Although family/friends are often a major source of social support post-injury, future efforts are needed to increase social support from one's team, which in turn may help mitigate the risk of depression and anxiety post-injury. Significance: Social support from family/friends or one's team post-injury may help college student-athletes cope with the psychological impact of injury, reducing post-injury depression and anxiety symptoms.